Corrigendum to “The impact of photovoice on the report of emotions in individuals with persistent physical symptoms: Results of an experimental trial” [Journal of Psychosomatic Research 191 (2025) 112069] (Journal of Psychosomatic Research (2025) 191, (S0022399925000339), (10.1016/j.jpsychores.2025.112069)) - Studer, Selina; Nuhn, Christina; Weise, Cornelia; Kleinstäuber, Maria (Journal of Psychosomatic Research, 2025)
The authors regret that in the original version of this article an error occurred in the affiliation details for one of the authors, Cornelia Weise. Specifically, the primary and secondary affiliations for that author were inadvertently interchanged. The correct affiliations for the affected author are as follows: Primary Affiliation: Department of Psychology, Clinical Psychology and Behavioral Health Technology, Friedrich-Alexander-Universität Erlangen-Nürnberg, Erlangen, Germany. Secondary Affiliation: Department of Psychology, Division of Clinical Psychology and Psychotherapy, Philipps-University Marburg, Marburg, Germany. This correction does not affect the content or conclusions of the article. The authors would like to apologise for any inconvenience caused.
CRIS-Team Scopus Importer:2025-04-01